Black Soldier Fly (Hermetia illucens L.) Larvae Oil Ointment to Accelerate Incision Wound Healing in Mice - Afriani, Yona; Rahayu, Resti; Santoso, Putra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Larvae of the Black Soldier Fly (BSF) are a natural material that has the potential to become a new alternative for accelerating wound healing due to their nutritional content. This study aims to analyze the potential of BSF larvae oil ointment in accelerating the healing of incisional wounds in mice. The study was conducted as an experimental research with six treatments and four repetitions, including a control group without treatment, ointment base, gentamicin ointment, BSF larvae oil ointment at 5% concentration, BSF larvae oil ointment at 10% concentration, and BSF larvae oil ointment at 15% concentration. The parameters observed included the percentage of wound healing, area under the curve (AUC) values, and anti-inflammatory efficacy percentage. The results showed no significant differences between groups based on statistical analysis (P>0.05) for the observed parameters. However, the 5% BSF larvae oil ointment showed a 100% healing percentage on the fourteenth day. Based on AUC values and anti-inflammatory efficacy percentage, the 5% BSF larvae oil ointment had values close to commercial gentamicin ointment. This indicates that treatment with BSF larvae oil ointment, especially at the lowest dose, plays a role in accelerating incisional wound healing and has great potential to be developed as a commercial ointment in the future.